Le permafrost de montagne et les processus géomorphologiques associés : évolutions récentes dans les Alpes françaises - Xavier Bodin; Philippe Schoeneich; Philip Deline; Ludovic Ravanel; Florence Magnin; Jean-Michel Krysiecki; Thomas Echelard (Revue de Géographie Alpine)
Alpine mountains are affected by significant geomorphological processes whose evolution is partly conditioned by permafrost warming: rockfalls of various volumes, destabilisation of rock glaciers, and cryokarst. These phenomena, because of their intensity, may generate risks for territories. This paper provides a synthesis of the knowledge about the current status of the mountain permafrost in the French Alps and its recent evolution. This state-of-the-art overview is based on research conducted over the past 10 years and the measurements collected within PermaFRANCE, the French network for long-term observation of the mountain permafrost. The analysis of the available data shows that for a rock wall located at 3800 m asl., the temperature is between -4.5 and -1.5°C at a depth of 10 m, according to the aspect, whereas it is close to the melting point in surficial deposits at 2800 m asl. on a northern slope. Since the beginning of these measurements at depth in 2010, a trend of increasing temperature has been discernible, as found in other alpine boreholes. As clearly shown by the surface measurements conducted since 2003, the thermal regime is influenced by snow, particularly in surficial deposits and to a much lesser extent in rock walls. This inter-annual variability is combined with longer-term trends, which probably induce the observed changes in geomorphological dynamics associated with alpine permafrost: an increased frequency of gravitational processes such as rockfalls and fluctuation in rock glacier velocities. The possible increase in extreme events, such as rock avalanches or the destabilisation of rock glaciers, in the coming decades could create new or increased risks, to which territories must thus adapt.